Single Sitting Surgical Treatment of Generalized Aggressive Periodontitis Using GTR Technique and Immediate Implant Placement with 10-Year Follow-Up - Fatme Mouchref Hamasni; Fady El Hajj; Rima Abdallah (Case Reports in Dentistry)
This case report exhibits a patient with generalized aggressive periodontitis who has been under maintenance for the past 12 years after being surgically treated in a single sitting and restored with dental implants. A 41-year-old systemically healthy male patient presented complaining of lower anterior teeth mobility and pain in the upper right quadrant. After clinical and radiographic examination, the upper right molars and lower anterior incisors were deemed unrestorable. Covered by doxycycline, the patient received a nonsurgical periodontal treatment. Three weeks later, teeth extraction, immediate implant placement, immediate nonloading provisional prosthesis, and a guided tissue regeneration were performed at indicated areas in a single sitting. The clinical decisions were based on patient compliance, the status of the existing periodontal tissues, and the prognosis of the remaining teeth. During the 12-year follow-up period, no residual pockets were observed and there was no exacerbation of the inflammatory condition. Marginal bone stability is present on all implants. For aggressive periodontal disease, a high risk of relapse as well as limited success and survival of dental implants should be considered. This case shows proper containment of the disease based on appropriate treatment planning and a strict maintenance program.